PUDARNYA BUDAYA SOPAN SANTUN MASYARAKAT INDONESIA DALAM MENGEMUKAKAN PENDAPAT DI MEDIA SOSIAL - Irishtsany Indira Laily Nurdin; Davelynn Danielle; Dwianputra Kresnadi Purbanegara; Neira Ramadhania; Mohammad Indie Farhan; Pandu Ridhana (Journal of Development and Social Change, 2021)
Indonesia is well-known as a country known for its culture of courtesy. But along with the times, the culture seems to be fading, especially on social media. Therefore, the researcher wants to know the causes of the loss of the culture of courtesy and reveal how social media affects the politeness of the Indonesian people in expressing opinions. The method used in this study is a qualitative method with data collection techniques through surveys and literature studies. Through the research conducted, researchers found that the Indonesian people ignore the aspects of courtesy in expressing opinions on social media due to several factors, including anonymity, the bias in the notion of freedom of opinion, exemption of personal problems in the real world, and the absence of specific regulations governing limitations in having opinion on social media. Social media has a significant effect on changing attitudes and views of Indonesian society towards the concept of courtesy and courtesy in expressing opinions. Researchers found that there is a double standard in the definition of polite in social media and the real world. Researchers hope that this research can add insight and become material for community consideration in expressing their opinions on social media and the real world.